596 Redeployment of Surgical Trainees to Intensive Care During the COVID-19 Pandemic: Evaluation of the Impact on Training and Wellbeing. (12th October 2021) - Payne, A; Alfa-Wali, M; Rahman, R; Bullingham, R; Vamadeva, S
Abstract: Aim: The aim of this study was to evaluate the impact of redeployment of surgical trainees to intensive care units (ICUs) during the COVID-19 pandemic in terms of transferrable technical and nontechnical skills and wellbeing. Method: This was a survey study consisting of a 23-point questionnaire. The study involved senior house officer level surgical trainees that had been redeployed to the (ICU) across all hospitals in London during the COVID-19 pandemic. The survey was sent to 90 surgical trainees. Thirty-two trainees responded to the questionnaire and were included in the study results. Results: All respondents spent between 4 and 8 weeks working in ICU. Prior to redeployment, 78% of participants had previous experience of ICU or an affiliated specialty, and >90% had attended at least 1 educational course with relevance to ICU. There were statistically significant increases in confidence performing central venous cannulation and peripheral arterial catheterisation (p < 0.05). With regards to clinical skills, respondents reported feeling more confident managing ventilated patients, patients on noninvasive ventilation, dialysis, and circulatory failure patients after working in ICU. Respondents (97%) felt that the experience would be beneficial to their future careers but 53% felt the redeployment had a negative impact on their mental health. Conclusions: Redeployment of surgical trainees to ICU led to increased confidence in a number of technical and nontechnical skills. However, proactive interventions are needed for training surgeons with regard to their psychological wellbeing in these extraordinary circumstances and to improve workforce planning for future pandemics.